Effectiveness of hyperbaric oxygen therapy for wound healing in patient with diabetic foot ulcer: a mini review - Ahdiah, Nurul; Junaidi, Gito; haris, Novit; Jamaludin, Thandar Soe Sumaiyah (IIUM Press, 2019)
Diabetes mellitus (DM) is a metabolic disease in which the body has difficulty producing insulin which leads to high blood glucose levels. Consequently, people suffering from DM can have damage organs, blood vessels, and nerves which resulting in getting diabetic foot ulcer (DFU). Other therapeutic interventions are offered if the DFU does not heal with normal standard wound care. One of which is hyperbaric oxygen therapy (HBOT) that will increase the oxygen supply to wounds. However, the effectiveness of this therapy is not clearly known till present. Thus, the review of this paper aimed to report on the results of analysis of research that focuses on the effect HBOT on diabetic foot ulcer healing. Relevant literature was searched in Google Scholar and PubMed used keywords “hyperbaric oxygen therapy" "diabetic foot ulcer" "wound healing", and “chronic ulcer”. Five articles that met the inclusion criteria based on the results of the analysis. Although there was some indication of a beneficial effect of wound healing process, it is currently unknown which patients are likely to benefit from HBOT and which patients are not.